Exploring the Impact of Single-Nucleotide Polymorphisms on Translation - Robert, Francis; Pelletier, Jerry (Frontiers in Genetics, 2018)
Over the past 15 years, sequencing of the human genome and The Cancer Genome Atlas (TCGA) project have led to comprehensive lists of single-nucleotide polymorphisms (SNP) and gene mutations across a large number of human samples. However, our ability to predict the functional impact of SNPs and mutations on gene expression is still in its infancy. Here, we provide a framework to help understand how mutations present in genes can affect translational output.